SERINC5 Inhibits the Secretion of Complete and Genome-Free Hepatitis B Virions Through Interfering With the Glycosylation of the HBV Envelope - Liu, Yue; Wang, Hong; Zhang, Jun; Yang, Jing; Bai, Lu; Zheng, Baisong; Zheng, Tianhang; Wang, Yingchao; Li, Jianhua; Zhang, Wenyan (Frontiers in Microbiology, 2020)
Serine incorporator 3 (SERINC3) and SERINC5 were recently identified as host intrinsic factors against HIV-1 and counteracted by HIV-1 Nef. However, whether they inhibit hepatitis B virus (HBV), which is a severe health problem worldwide, is unknown. Here, we demonstrate that SERINC5 potently inhibited HBV virion secretion in the supernatant without affecting intracellular core particle-associated DNA and the total RNA, but SERINC3 and SERINC1 did not. Further investigation discovered that SERINC5 increased the non-glycosylation of LHB, MHB and SHB proteins of HBV and slightly decreased HBs proteins levels, which led to the decreased HBV secretion. Importantly, SERINC5 co-localized with LHB proteins in the Golgi apparatus, which is important for glycan processing and transport. In addition, we determined the functional domain in SERINC5 required for HBV inhibition, which was completely different from that required for HIV-1 restriction, whereas phosphorylation and glycosylation sites in SERINC5 were dispensable for HBV restriction. Taken together, our results demonstrate that SERINC5 suppresses HBV virions secretion through interfering with the glycosylation of HBV proteins, suggesting that SERINC5 might possess broad-spectrum antiviral activity.